The Urban and the Empty Spaces in the Amazon as Elements in the Production of National Cartographies in Colombia - Aponte, Jorge (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The representations that we traditionally have of the Amazon omit or minimize the urban phenomena that have been a fundamental part of its territorial configuration, leaving us the image of “empty spaces”, “incognito” or “wild”, which contain lush jungles, widely diverse in fauna and flora but that have no owners or civilized inhabitants. Therefore their wealth can be exploited by those who describe the territory. However, these same spaces are internally demarcated by populations that at least in the cartographic representation call into question the emptying discourse, evidencing that the construction of these voids is framed by disputes over territorial control, in which, delete or not to represent human forms of habitation, as well as the establishment of urban enclaves, either in practice or only in representation, they are functional in the exercise of territorial appropriation. In this sense, as part of the exploratory start of this investigation, I will reflect on the role of the city in the Amazonian space production and the forms as the urban has been represented both within the framework of the disputes associated with the consolidation of the territorial spaces state -nationals in the Amazon, particularly emphasizing the symbolic exercises of representing Colombia in the Amazon. For this, we will work from the analysis and deconstruction of the map, following the methodological proposal of Bryan Harley (2005), trying to understand the senses and reasons of the iconographic representation of the urban in some maps that include the Amazon region at the end of the 19th century